Efficient Photosensitizer Delivery by Neutrophils for Targeted Photodynamic Therapy of Glioblastoma - Ruojian Wen; Yuwei Liu; Xiang Tian; Yonghong Xu; Xiao Chen (Pharmaceuticals)
Background/Objectives: Glioblastoma (GBM) is the deadliest type of brain tumor and photodynamic therapy (PDT) is a promising treatment modality of GBM. However, insufficient photosensitizer distribution in the GBM critically limits the success of PDT. To address this obstacle, we propose tumoritropic neutrophils (NE) as active carriers for photosensitizer delivery to achieve GBM-targeted PDT. Methods: Isolated mouse NE were loaded with functionalized hexagonal boron nitride nanoparticles carrying the photosensitizer chlorin e6 (BNPD-Ce6). In vitro experiments were conducted to determine drug release from the loaded NE (BNPD-Ce6@NE) to mouse GBM cells and consequential photo-cytotoxicity. In vivo experiments were performed on mice bearing intracranial graft GBMs to demonstrate GBM-targeted drug delivery and the efficacy of anti-GBM PDT mediated by BNPD-Ce6@NE. Results: BNPD-Ce6@NE displayed good viability and migration ability, and rapidly released BNPD-Ce6 to co-cultured mouse GBM cells, which then exhibited marked reactive oxygen species (ROS) generation and cytotoxicity following 808 nm laser irradiation (LI). In the in vivo study, a single intravenous bolus injection of BNPD-Ce6@NE resulted in pronounced Ce6 distribution in intracranial graft GBMs 4 h post injection, which peaked around 8 h post injection. A PDT regimen consisting of multiple intravenous BNPD-Ce6@NE injections each followed by one extracranial tumor-directed LI 8 h post injection significantly slowed the growth of intracranial graft GBMs and markedly improved the survival of host animals. Histological analysis revealed massive tumor cell damage and NE infiltration in the PDT-treated GBMs. Conclusions: NE are efficient carriers for GBM-targeted photosensitizer delivery to achieve efficacious anti-GBM PDT.